American's dream - Santiago, Esmeralda (New York : HarperCollins Publishers, 1997)
America as seen through the eyes of a Puerto Rican maid. She is America Gonzalez, brought over by a Westchester, New York, couple who met her in a hotel in Puerto Rico where she was a cleaner. A novel filled with insights and observations by the author of When I Was Puerto Rican.
Keywords: DOMESTIC FICTION